Calcined bone provides a reliable substrate for strontium isotope ratios as shown by an enrichment experiment - Snoeck, C; Lee-Thorp, J; Schulting, R; de Jong, J; Debouge, W; Mattielli, N (Wiley, 2014)
Rationale Strontium isotopes (87Sr/86Sr) are used in archaeological and forensic science as markers of residence or mobility because they reflect the local geological substrate. Currently, tooth enamel is considered to be the most reliable tissue, but it rarely survives heating so that in cremations only calcined bone fragments survive. We set out to test the proposition that calcined bone might prove resistant to diagenesis, given its relatively high crystallinity, as the ability to measure in vivo 87Sr/86Sr from calcined bone would greatly extend application to places and periods in which cremation was the dominant mortuary practice, or where unburned bone and enamel do not survive.